Experimental petrology of the Tissint meteorite: Redox estimates, crystallization curves, and evaluation of petrogenetic models. (14th October 2016) - Castle, Nicholas; Herd, Christopher D. K.
Abstract: Tissint is an olivine‐phyric shergottite from an incompatible element depleted Martian mantle source. Oxythermobarometry applied to Tissint mineral phases demonstrates that the Tissint magma underwent an increase in oxygen fugacity, from 3.5 log units below the quarz‐fayalite‐magnetite (QFM) buffer during the early stages of crystallization, to QFM−1.4 during the latter stages. This is the first time that such an oxidation event has been observed in a depleted shergottite. The reason for the oxidation event is unclear; however, calculations using the MELTS thermodynamic model suggest that auto‐oxidation is insufficient to cause more than 1 log unit of oxidation, and therefore an external oxidation mechanism—such as oxidation by degassing—is required. If volatiles are responsible for the oxidation, then it indicates that volatiles are not exclusively tied to the enriched Martian mantle reservoir. A series of experiments using the Tissint parental magma were carried out under fixed (isothermal) or variable (cooling rate) temperature control, and at either reducing (QFM−3.2) or oxidizing (QFM−1) redox conditions. The observed liquid line of descent supports a potential genetic relationship between basaltic shergottites and olivine‐phyric shergottites. A peritectic relation where olivine is resorbed to form pyroxene is favored by increased oxygen fugacity; if oxidation during crystallization is more common than presently believed, it may explain why olivine is typically anhedral in olivine‐phyric shergottites. Results from a cooling‐rate experiment in which the oxygen fugacity was changed during the latter stages of crystallization resulted in olivine with a Cr compositional profile consistent with oxidized isothermal experiments, despite forming primarily under reducing conditions. A similar profile is observed in Tissint olivines, consistent with its redox history. Our results provide insights into the potential influence of oxidation events on the compositional zoning of minor or trace elements in olivine in olivine‐phyric basalts.